2021
DOI: 10.1152/ajpheart.00477.2021
|View full text |Cite
|
Sign up to set email alerts
|

Stop the beat to see the rhythm: excitation-contraction uncoupling in cardiac research

Abstract: Optical mapping is an imaging technique that is extensively used in cardiovascular research, wherein parameter-sensitive fluorescent indicators are used to study the electrophysiology and excitation-contraction coupling of cardiac tissues. Despite the many benefits of optical mapping, eliminating motion artifacts within the optical signals is a major challenge, as myocardial contraction interferes with the faithful acquisition of action potentials and intracellular calcium transients. As such, excitation-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 91 publications
(121 reference statements)
0
31
0
Order By: Relevance
“…In isolated rabbit hearts, right ventricular and atrial tissue, and in rat ventricular myocytes, it was first shown that blebbistatin has no effect on SAN activity or on cardiomyocyte APD ( Fedorov et al, 2007 ). Since that time, studies using rabbit hearts have confirmed a lack of an effect of blebbistatin on APD, while later studies using rabbit and pig hearts have demonstrated an increase ( Swift et al, 2021 ). The increase in APD that we observed in the zebrafish atrium agrees with these later findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In isolated rabbit hearts, right ventricular and atrial tissue, and in rat ventricular myocytes, it was first shown that blebbistatin has no effect on SAN activity or on cardiomyocyte APD ( Fedorov et al, 2007 ). Since that time, studies using rabbit hearts have confirmed a lack of an effect of blebbistatin on APD, while later studies using rabbit and pig hearts have demonstrated an increase ( Swift et al, 2021 ). The increase in APD that we observed in the zebrafish atrium agrees with these later findings.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in APD that we observed in the zebrafish atrium agrees with these later findings. It is unclear whether this increase in APD is due to non-specific interactions of blebbistatin with cardiac ion channels and/or transporters or is instead a secondary effect of the loss of contraction caused by excitation-contraction uncoupling, for instance due to a loss of mechano-electric coupling effects or to a decrease in sarcolemmal ATP-sensitive K + channel current caused by a decrease in metabolic demand ( Swift et al, 2021 ). The other electrophysiological findings in our study (decreased DD slope in the SAN and increased APD in the ventricle) suggest there may be direct effects of blebbistatin on ion channels and/or transporters, warranting further investigations to determine the specific mechanism(s) involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motion artifacts arise quickly during optical mapping even with the slightest motion if the measurements are performed in an ordinary fashion: extracting and analyzing the optical signals pixel by pixel without numerical motion tracking ( 15 , 16 ). As a result, over the past 30 years, the motion has been avoided at all costs in optical mapping studies ( 17 ). To overcome this limitation, optical mapping has more recently been combined with numerical motion tracking and stabilization techniques to track and measure fluorescence on the deforming tissue surface in a co-moving reference frame, which effectively inhibits motion artifacts ( 6 , 16 , 18 20 ).…”
Section: Introductionmentioning
confidence: 99%